The World Book encyclopedia. (Chicago World Book, 1989)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students.
Vol. 22 consists of research guide and index.
Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries